3D/4D printing of dental aligners via digital light processing - Heng, Bryan Jing Tong (Nanyang Technological University, 2024)
There has been a growing interest in implementing 4D-printed dental aligners for orthodontic treatment, which addresses the concerns of material wastage. This can be achieved by using Shape Memory Polymers (SMP), a material capable of returning to its original shape when exposed to heat. A recent study compared Graphy’s TC-85 4D printed aligner to conventional thermoplastics. It concluded that the TC-85 has better flexibility, reduced force loss, and shape memory capabilities. However, the TC-85 aligner lacks sufficient force to effectively displace the patient’s teeth. For the aligner to be reused, it must exert sufficient force at different displacements to simulate the alignment process. Doing so, required the manipulation of shape reset and programming temperatures of the SMP based on its Glass Transition temperature (Tg). By manipulating the temperatures using the Dynamic Mechanical Analyzer (DMA), the SMP was shown to produce different forces. The DMA results showed that a higher recovery force was generated when the SMP was programmed at a lower temperature. By using different programming temperatures, the SMP was able to generate similar force magnitudes across different displacements. This mechanism can be adopted for the use of the aligners, where the orthodontic forces can be maintained at an optimal magnitude regardless of the displacement. While limitations were present, further research can be done to reduce those limitations and produce better results. These include utilizing simulation software to deduce trends, further analyzing trends on the Double Cycle test, and reducing inconsistencies on prints.